Health seeking practices among the caretakers of mentally ill patients attending psychiatric OPD of Tribhuvan University. - Paudel, kamala (2012)
ABSTRACT: Statement: - Health Seeking Practices among the Care-takers of Mentally Ill Patients Attending Psychiatric OPD of T.U. Teaching Hospital, Maharajgunj. Objective: - The main objective of this study was to identify the health seeking practices among the care-takers of the mentally ill patients attending Psychiatric OPD of TUTH. Methodology: - A descriptive research study was conducted at Psychiatric OPD of TUTH Maharajgunj from 10th - 24th June, 2012, among fifty respondents. The sample was selected applying the purposive sampling technique. The information was collected by the interview technique using structured questionnaire tool and which consists four parts, first demography, second knowledge about mental illness, third belief on mental illness and fourth health practice. Result: The age of the respondents ranged from 20-69 years and a highest frequency of the respondents were from the age group 30-39 years i.e. eighteen (36%). Forty one (82%) were male and nine (18%) were female. Treatment options first employed by the majority of the respondents i.e. forty two (84%) had visited the psychiatrist only after seeking other health practices. The main reason for delay in treatment options employed were ignorance of mental illness (81%), ignorance of the existence of a mental health service (2%), ignorance of mental illness and health service (12%), lack of mental health facilities (5%) out of forty two (84%). The perception of the cause of the ailment most commonly revealed a belief in demonic and spiritual forces. Living in the urban area especially capital city, Kathmandu, were significantly associated with the employment of specialist care as the first treatment option. Conclusion: Ignorance of the mental illness and lack of awareness of mental health facilities still abound among the participants. Consequently, alternative sources of care are still employed. There is a need for community health education to demystify mental illnesses as well as to highlight the availability of mental health services. This education should create positive attitudes, correct misconceptions and encourage early specialist consultation and better treatment outcomes. Mental health services should be made available to rural dwellers by integrating them into existing primary health care services.